Export Subsidies as an Outcome of the Management-Labor Conspiracy - Matsuyama, Kiminori (Quarterly Journal of Economics, 1990)
Journal Article Export Subsidies as an Outcome of the Management-Labor Conspiracy Get access Kiminori Matsuyama Kiminori Matsuyama Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 3, August 1990, Pages 803–813, https://doi.org/10.2307/2937900 Published: 01 August 1990